Prevalence of respiratory morbidity among shopkeepers in the vicinity of a national highway, Bangalore - Ramesh, Naveen (International Journal of Occupational Safety and Health, 2017)
Background: Studies done in the West have shown adverse interaction between highway pollutants on cardio pulmonary health of the people working or residing close to the highways. Therefore a study was undertaken to document the respiratory morbidity among shopkeepers working in shops situated on national highway (NH) 7, Bangalore. Objectives: To study the prevalence of respiratory morbidity among shopkeepers on NH 7. Methodology: Cross sectional study was done among 121 randomly selected shopkeepers working for more than a year in shops located within 100 meter radius of a junction of NH 7, Bangalore. A pre-validated questionnaire was administered to the shopkeepers along with measurement of peak expiratory flow rate (PEFR), general physical and systemic examination. Results: Among the study participants, 59.5% was totally asymptomatic and classified as normal. Others were classified as syndrome of cough (32.2%), syndrome of breathlessness (31.4%), syndrome of asthma (12.4%) and syndrome of atopy (23.1%). Conclusions: The prevalence of respiratory morbidity and asthma was found to be significantly higher in shopkeepers near the highway than that of currently established data for residents of urban Bangalore. Presence of asthma in shopkeepers had a significant positive correlation with number of hours per day and years of exposure. Large prospective cohort studies could be undertaken to identify the effect of pollutants on the health of shopkeepers. Strengthening existing legislations could help reduce the effect of pollutants on health of shopkeepers working or residing near highways.